Answer:
[tex]x=0[/tex]
Step-by-step explanation:
[tex]\frac{7}{3}(2x+3)+\frac{3}{4}(\frac{x}{5}-\frac{15}{2})=\frac{11}{8}[/tex] <-- Given
[tex]\frac{14}{3}x+7+\frac{3}{20}x-\frac{45}{8}=\frac{11}{8}[/tex] <-- Distributive Property
[tex]\frac{280}{60}x+7+\frac{9}{60}x-\frac{45}{8}=\frac{11}{8}[/tex] <-- Find LCD of x-terms
[tex]\frac{289}{60}x+7-\frac{45}{8}=\frac{11}{8}[/tex] <-- Combine Like Terms
[tex]\frac{289}{60}x+7=\frac{56}{8}[/tex] <-- Add 45/8 to both sides
[tex]\frac{289}{60}x+7}=7[/tex] <-- Simplify Right Side
[tex]\frac{289}{60}x=0[/tex] <-- Subtract 7 on both sides
[tex]x=0[/tex] <-- Divide both sides by 289/60